An overview of brady dysrhythmias in the emergency department - Almalki, Somaia Khalid; Kulaib, Ghaidaa Mohammad; Alshareef, Raghad Naif; Alhawsawi, Abdulaziz Mousa; Alshammari, Ahmed Rafa; Alali, Mahdi Abdulmohsen; Alalawi, Ammar Hassan; Mughallis, Abdulrhman Ebrahim; Aljohani, Doaa Abdulaziz; Alhaeti, Haitham Rasheed; Turkistani, Mohammad Abdulhamid (International Journal Of Community Medicine And Public Health, 2022)
Bradyarrhythmias, which include physiological and pathological disorders such as sinus node dysfunction and atrioventricular conduction disturbances are frequent clinical findings in the emergency department. Although some benign bradyarrhythmias do not need treatment, acute unstable bradycardia can lead to cardiac arrest. A thorough history and physical examination should cover potential causes of sinoatrial node dysfunction or atrioventricular block in patients with confirmed or suspected bradycardia. Based on the severity of the symptoms, the underlying causes, the presence of possibly reversible causes, the presence of negative indications, and the danger of asystole progression, bradyarrhythmias are managed. Bradyarrhythmias that are unstable or symptomatic are treated with medication and/or pacing. Bradycardia is described as an adult heart rate of less than 60 beats per minute. Syncope, presyncope, momentary light-headedness or dizziness, exhaustion, dyspnea with exertion, heart failure symptoms, or disorientation brought on by cerebral hypoperfusion are typical signs of bradycardia. Atropine plays a significant role in the management of bradyarrhythmias because it counteracts the impact of the parasympathetic vagus nerve system, which can cause an increase in heart rate. Atropine administration is indicated in cases with vagus-mediated asystole, obstructions in the atrioventricular node, and sinus bradycardia. Installation of temporary pacemaker, permanent pacemaker is also among the effective management strategies of the bradyarrythmias. Diagnosis and management of bradyarrythmias in emergency department is of utmost importance since it can prevent morbidity and mortality. The purpose of this research is to review the available information about an overview of bradydysrhythmias in the emergency department.